A map of the altered glioma metabolism. Issue 11 (November 2021) - Deshmukh, Ruhi; Allega, Maria Francesca; Tardito, Saverio
Abstract : The frequent occurrence of neomorphic isocitrate dehydrogenase 1 ( IDH1 ) mutations in low-grade glioma led to an IDH-centric classification of these tumors. However, exploiting metabolic alterations of glioma for diagnostic imaging and treatment has marginally improved patients' prognosis. Here we discuss the nutritional microenvironment of glioma, shaped by the distinctive dependence of the brain on glucose and ketone bodies for energy, and on amino acids for neurotransmission. We highlight the progress in metabolic applications for glioma diagnosis and therapy, and present a map that streamlines the rewired glioma metabolism. The map illustrates the altered reactions in central carbon and nitrogen metabolism that drive glioma biology, and represent metabolic vulnerabilities with translational potential. Highlights: The neomorphic IDH1/2 mutations broadly perturb the metabolism of glioma cells, including their redox balance, but the oncogenic drive of the mutation seems to reside with the epigenetic effect of 2-HG. The avid uptake of glucose is a metabolic hallmark of the central nervous system that is maintained in glioma, impairing the detection of these tumors by 18 F-FDG PET. Naïve glioblastoma cells cultured in serum-free conditions express neural stem cell markers, but display metabolic features typical of differentiated astrocytes, such as glutamine synthesis. Glutamate metabolism is at the crossroad of glioma biology and neurotransmission.